Application of a game-theoretic multi-loop control system design with robust performance - Wellenreuther, Andrea; Gambier, Adrián; Badreddin, Essameddin (IFAC Proceedings Volumes, 2008)
Abstract:The game-theoretic view of control system design for multi-loop systems is extended in this work to ensure a closed-loop system with robust stability. The control system design is modeled as a differential cooperative game to incorporate interactions between the multiple loops of the control system. A robust stability indicator is formulated as an additional cost function. The developed approach is applied to a reverse osmosis desalination plant with different constraint settings on the control signals. The solution of the game provides Pareto-optimal sets, depending on the control signal constraints. Single points are chosen from the Pareto-optimal sets resulting in controller parameters leading to a reverse osmosis system with optimal performance concerning the error convergence, control effort and robust stability.
Gesehen am 24.04.2019